Production of annual winter forage sown before and after soybean harvest under different nitrogen fertilization levels - Migliorini, Francisco; Soares, André Brugnara; Sartor, Laércio Ricardo; Adami, Paulo Fernando; Pattis, Carlos Alberto; Migliorini, Patricia (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effect on forage yield of sowing winter forage species before and after soybean harvest, at different nitrogen application levels. The experiment was set out in a randomized block design with a strip-split plot arrangement, and three replicates. Sowing methods (18 days before soybean harvest and six days after soybean harvest) were allocated in the main plots, and the combination among forage species (Avena strigosa cv. IAPAR 61 + Lolium multiflorum; A. strigosa cv. Comum + L. multiflorum; A. strigosa cv. Comum + L. multiflorum + Vicia villosa; A. strigosa cv. Comum + L. multiflorum + Raphanus sativus; and L. multiflorum) and nitrogen levels (0, 140, 280 and 420 kg ha-1) in the plots and subplots, respectively. Forage sowing before the soybean harvest made it possible to anticipate first grazing by 14 days, with satisfactory establishment of forage species without affecting forage production. This method permitted a longer grazing period, preventing the need for soil disking, besides allowing the use of no-tillage system. The mixture of forage species enables higher forage yield for pasture in relation to single species pastures, with response to nitrogen fertilization up to 360 kg ha-1.